2016
DOI: 10.1039/c5ra25688g
|View full text |Cite
|
Sign up to set email alerts
|

Stereocomplex poly(lactic acid) nanoparticles crystallized through nanoporous membranes and application as nucleating agent

Abstract: Stereocomplex crystallization of poly(l-lactic acid) (PLLA) and poly(d-lactic acid) (PDLA) was performed by flowing their blended solution through nano-channels of porous membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…27 In another study, PLLA/PDLA nanoparticles were reported to contain alpha-type crystals. 38 Aer annealing, the molten alphatype crystals were cold crystallized to form pure SC-type nanoparticles, which served as nucleating agents for PLLA matrix crystallization and signicantly shortened the crystallization time of the pure PLLA matrix. For example, when a PLLA lm was cooled from the molten state to induce non-isothermal crystallization, the addition of 1% PDLA effectively shortened the PLLA crystallization time.…”
Section: Introductionmentioning
confidence: 99%
“…27 In another study, PLLA/PDLA nanoparticles were reported to contain alpha-type crystals. 38 Aer annealing, the molten alphatype crystals were cold crystallized to form pure SC-type nanoparticles, which served as nucleating agents for PLLA matrix crystallization and signicantly shortened the crystallization time of the pure PLLA matrix. For example, when a PLLA lm was cooled from the molten state to induce non-isothermal crystallization, the addition of 1% PDLA effectively shortened the PLLA crystallization time.…”
Section: Introductionmentioning
confidence: 99%
“…This approach offers promising potential for scale‐up production of biomineralized nanomaterials. This precipitation extrusion method has been further extended for preparing composite nanomaterials from other biomaterials including fibronectin, elastin, hyaluronan, and PLA . For example, Raoufi et al reported the use of precipitation extrusion to prepare a variety of biopolymer blended nanofibers with an AAO membrane .…”
Section: Nanoporous Membrane Extrusion Strategiesmentioning
confidence: 99%
“…They blended poly(L‐lactic acid) and poly( d ‐lactic acid) in chloroform as feed solution and extruded it through 100 nm PCTE or AAO membrane into a methanol receiver solution. Owing to the insolubility of PLA in methanol, stereocomplex nanoparticles were precipitated . Interestingly, Powell et al observed the phenomenon of transient precipitation and dissolution process of calcium hydrogen phosphate nanoparticles inside a conical‐shaped nanopore of a PET membrane .…”
Section: Nanoporous Membrane Extrusion Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, utilizing stereocomplex would transform PLLA monoliths into a high‐performance porous material, which can be used in various fields mentioned above with no difficulty. Although formations of gel, particle, and porous surface using sc‐PLA have been studied previously, there has been no report so far that investigates a monolithic pure sc‐PLA. Moreover, a phase separation technique combined with setereocomplexation between enantiomeric polymers has not been developed until now despite the fact that a variety of monoliths are now mainly fabricated through phase separation because of its simplicity and processability.…”
Section: Introductionmentioning
confidence: 99%